2010
DOI: 10.1088/0022-3727/43/31/315301
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear behaviour of electrostatically actuated carbon nanotube-based devices

Abstract: In this paper nonlinear behaviour of electrostatically actuated carbon nanotubes (CNTs) is investigated. The model comprises a clamped–clamped CNT suspended over a graphite ground electrode plate from which a potential difference is imposed. The actuation is based on ac and dc applied voltages and it is assumed that the neutral axis of bending is stretched when the beam is deflected, and also, the interatomic interaction forces between CNT and ground plate are considered. The versatile Galerkin's method is emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Consequently, carbon nanotubes were shown to be sole components to build new artificial muscles thanks to their giant elongations and elongation rates, respectively [38]. Furthermore, and in addition to extending the capabilities of artificial muscles to giant strokes and strain rates at extreme temperatures, CNT-based actuator mechanisms provide other possible applications that relate to its light-emitting displaying ability [38], switching capabilities [39,40], transducing and oscillating capacities [41][42][43], and largestroke actuation competencies [44][45][46][47][48][49][50][51][52].…”
Section: Large-stroke Cnt-based Nems Devicesmentioning
confidence: 99%
“…Consequently, carbon nanotubes were shown to be sole components to build new artificial muscles thanks to their giant elongations and elongation rates, respectively [38]. Furthermore, and in addition to extending the capabilities of artificial muscles to giant strokes and strain rates at extreme temperatures, CNT-based actuator mechanisms provide other possible applications that relate to its light-emitting displaying ability [38], switching capabilities [39,40], transducing and oscillating capacities [41][42][43], and largestroke actuation competencies [44][45][46][47][48][49][50][51][52].…”
Section: Large-stroke Cnt-based Nems Devicesmentioning
confidence: 99%
“…Dequesnes et al (2002Dequesnes et al ( , 2004 investigated the deflection and the static pull-in of CNTs under electrostatic actuation considering the Van der Waals force. Rasekh and Khadem (Rasekh et al 2010) studied the static and dynamic behaviour of CNTs under the electrostatic and Van der Waals force. Ouakad and Younis (2010) studied the nonlinear dynamics of CNTs with the clamped-clamped and the cantilever boundary conditions under DC and AC electrical excitations.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that increasing the level of the initial curvature increases the amplitude, and decreases the pull-in DC voltage. Rasekh et al [31] used ROM to simulate the static and dynamic behavior to include the pull-in phenomenon of CNT bridges under DC and AC voltage actuation. The increase of the initial gap distance resulted in an increase of the pull-in voltage.…”
Section: Introductionmentioning
confidence: 99%